Design of Virtual Reality-Based Mathematics Virtual Lab with Constructivist Approach in Senior High School - Achmad Buchori; Noviana Dini Rahmawati; Wijayanto (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
The purpose of this research is to produce a virtual reality-based high school mathematics virtual lab product with a constructivistic approach in an effort to improve the literacy and numeracy of high school students. The research method uses R&D by adopting the ADDIE model, namely Analysis (Analyze), Design (Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluate). Researchers only conducted basic research so that the research stages only reached development. Data collection techniques used tests, questionnaires, structured interviews, and documentation. Data analysis used questionnaire analysis of student and teacher responses, feasibility analysis by experts, reduction of structured interview results and triangulation techniques. Test data was analysed using descriptive statistics. The results of this study are the production of virtual high school mathematics lab products as much as 10 materials that are attractively packaged based on virtual reality that have been validated by material experts and media experts with an average score of material experts = 89.70 and media experts = 90.38, meaning that this virtual mathematics lab product is very feasible to use in learning high school mathematics.